NEW CONSUMER AND MARKETING PATTERNS IN THE POST-PANDEMIC SCENARIO ARE PAVING THE WAY FOR THE SDGS IMPLEMENTATION - Hendra, Hendra (Universitas Dharma Wacana, 2023)
In the post-pandemic era, this essay examines how sustainable marketing and consumption models might help advance the implementation of the Sustainable Development Goals (SDGs). The study is motivated by the need for innovative solutions to decrease the negative consequences of the COVID-19 situation on global sustainability programs. The report synthesizes current research on sustainability marketing, the circular economy, and sustainable business strategies using a systematic literature review approach. The results show that sustainable marketing techniques can significantly impact consumer behavior and promote more environmentally friendly production and consumption patterns. The circular economy concept, which emphasizes resource efficiency and waste minimization, can also aid in sustainable development by fostering new economic opportunities and halting environmental damage. In order to encourage more sustainable practices in the post-pandemic era, the paper offers ideas for businesses and policymakers on how to incorporate sustainable marketing and circular economy principles into their plans. The study adds to the growing body of knowledge on the circular economy and sustainability marketing by pointing out possible avenues for encouraging sustainable consumption and production, which are crucial for reaching the SDGs